Jawabanmu

2014-08-27T20:28:32+07:00
1.2x.3x 2x.-4 3.3x 3.-4 =6x^-8x+9x-12 =6x^+x-12 2.3x.2x 3x.3 -4.2x -4.3 =6x^+9x-8x-12 =6x^+x-12 3.x.4x x.-2y -y.4x -y.-2y =4x^-2xy-4xy+2y^ =4x^-6xy+2y^ 4.4x.x 4x.-y -2y.x -2y.-y =4x^-4xy-2xy+2y^
Jawaban paling cerdas!
2014-08-27T20:51:59+07:00
1. (2x + 3) + (3x - 4) = 2x + 3x + 3 - 4 = 5x - 1
2. (3x - 4) + (2x + 3) = 3x + 2x - 4 + 3 = 5x - 1
3. (x - y) + (4x - 2y) = x + 4x - y - 2y = 5x - 3y
4. (4x - 2y) + (x - y) = 4x + x - 2y - y = 5x - 3y
5. (a + 3b) + (3a - b) = a + 3a + 3b - b = 4a + 2b
6. (3a - 6) + (a + 3b) = 3a + a - 6 + 3b = 4a - 6 + 3b

Maaf kalau salah
aku smpn 249
daerah mana itu?
jakarta
ow.. udh tau jwbn nya? ada fb/twitter?
udah